UIG Collaboration in Malaysia: The Significance of Intermediary Organization - Zakaria, Fadzly; Nasruddin, Ellisha (School of Social Sciences, USM, 2017)
In recent years, there has been a huge debate among researchers in identifying the best University- Industry-Government (UIG) partnership model which could drive innovation. The problems with UIG collaboration are due to differences in objectives, functions, and mechanisms among stakeholders, therefore such collaboration is difficult to form and sustain. A review of relevant literature and critical insights related to the topics from various management theories/ models are discussed in this paper. Some researchers suggested the concept of Triple Helix Model (TH) where UIG should work together as a team to create innovative and successful outcomes. Innovation is one of the national agendas in increasing the quality and productivity of our economic growth through strategic partnership. The government has introduced intermediary organization to harness the collaboration amongst UIG where it plays a crucial role in facilitating the TH. Therefore, this paper aims to further elaborate the significance of intermediary organizations in stimulating the TH. It also incorporates the concept of strategic partnership and innovation which become crucial tasks for intermediary organization in promoting synergic collaboration. Moreover, it analyses the correlation between the development phase of TH and innovation process by identifying the blockages or gaps in the existing system. This paper contributes towards a sustainable partnership framework and provides a solution for innovation creation especially in managing stakeholders’ involvement by explaining why and how collaborative intermediary organizations can facilitate the dynamic and synergy of collaboration, hence moving towards innovation.